2001
DOI: 10.1021/ma992182r
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation Kinetics of a Polymer Blend Modified by Random and Block Copolymer Additives

Abstract: The phase separation behavior of polymer blends modified by copolymer additives has been studied using light scattering techniques. Block and random copolymers with equal styrene and butadiene content as well as a random copolymer with unequal monomer composition were used as additives at a concentration of 2.5% (w/w). The symmetric additives lowered the phase boundary with increasing concentration while the asymmetric additive destabilized the phase boundary. The data demonstrate a slowing of the kinetics wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
2
24
1
Order By: Relevance
“…The process that is dominant in this technique is the segregation of the copolymer from a blend to a biphasic interface. Many studies have investigated the surface and interfacial properties of polymer blend thin films, including wetting phenomena, surface and interfacial segregation, and phase separation 17–39. In the case of surface segregation, small differences in the surface energy between the components can drive the segregation process of the lower surface energy component of a polymer blend to an interface.…”
Section: Introductionmentioning
confidence: 99%
“…The process that is dominant in this technique is the segregation of the copolymer from a blend to a biphasic interface. Many studies have investigated the surface and interfacial properties of polymer blend thin films, including wetting phenomena, surface and interfacial segregation, and phase separation 17–39. In the case of surface segregation, small differences in the surface energy between the components can drive the segregation process of the lower surface energy component of a polymer blend to an interface.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] In addition to these methods, cloud-point, dielectric relaxation spectroscopy, and temperature-jump light-scattering and rheometry measurements have also been widely used to investigate PIPS in thermosets. [30][31][32][33][34] Jyotishkumar et al 24 traced the dynamics of phase separation and the final morphologies of a poly(acrylonitrile-butadiene-styrene) (ABS) modified diglycidyl ether of bisphenol A (DGEBA) epoxy system in situ with OM, DSC, rheometry, and small-angle laser light scattering. AFM investigations of ABS showed that the crosslinked polybutadiene (PB) phase was dispersed in the SAN continuous phase.…”
Section: Overview Of Methods Used To Study the Pips Of Thermosetsmentioning
confidence: 99%
“…Another approach to prepare material with unique properties that combines the advantages of two or more polymers is the blending method, which uses conventional mixing technologies with much lower costs than copolymerization. [24,[30][31][32][33][34] The membrane of a PVAm/ poly(ethylene glycol) (PEG) (9:1) blend, for example, showed significantly increased CO 2 permeability and selectivity against CH 4 than the pure PVAm membrane, because the addition of PEG inhibits the crystallization of PVAm that prevents gas transport. [35] In this study, we prepared a series of hydrogel films by modified PVAm and tested the amount of CO 2 released in the low temperature (75 °C) regeneration process after absorbing CO 2 at 30 °C.…”
Section: Introductionmentioning
confidence: 99%